1976
DOI: 10.1111/j.1365-2427.1976.tb01601.x
|View full text |Cite
|
Sign up to set email alerts
|

The feeding relationships of two invertebrate predators in a New Zealand river

Abstract: SununaryThe size frequency distributions and foods of the larvae of Archichatdlodes diversus (Megaloptera: Corydalidae) and Stenoperia prasina {Plecoptera: Eustheniidae) were studied for a year in the Glenttd River, South Island, New Zealand. These two species are the largest invertebrate predators inhabiting .streams and rivers in New Zealand, where they are the only carnivorous members of their respective orders. Both species occttpied the same habitat with A. diversus being slightly more abundant in most mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 15 publications
(18 reference statements)
0
21
0
Order By: Relevance
“…Moreover, because N. serricornis fed primarily on philopotamids and polycentropodids while R. atratulus fed on hydropsychids, the extent of diet overlap between these two predators is even lower than is suggested by the overlap figure. We suggest that there is partitioning of prey resources by these predators. Few studies of predacious aquatic insects have gone beyond a single taxonomic order (exceptions are Devonport and Winterbourn, 1976;Hildrew and Townsend, 1976) and therefore comparisons have not been made between predator morphologies and foraging behavior among different insect orders. Investigations of stoneflies have shown that predator size may be more important than species differences, since small perlodid stoneflies have diets that are similar to smaller size classes of other, large predacious stoneflies (e.g., Isoperla filva versus Classenia sabulosa by Fuller andStewart, 1977, 1979).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, because N. serricornis fed primarily on philopotamids and polycentropodids while R. atratulus fed on hydropsychids, the extent of diet overlap between these two predators is even lower than is suggested by the overlap figure. We suggest that there is partitioning of prey resources by these predators. Few studies of predacious aquatic insects have gone beyond a single taxonomic order (exceptions are Devonport and Winterbourn, 1976;Hildrew and Townsend, 1976) and therefore comparisons have not been made between predator morphologies and foraging behavior among different insect orders. Investigations of stoneflies have shown that predator size may be more important than species differences, since small perlodid stoneflies have diets that are similar to smaller size classes of other, large predacious stoneflies (e.g., Isoperla filva versus Classenia sabulosa by Fuller andStewart, 1977, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…The fish studies can be further divided into investigations of single species (usually associated with fish life histories) or more commonly, of coexisting species; the latter investigations usually examine diets of congeners (e.g., Adamson and Wissing, 1977;Allan, 1978), or may characterize diets of entire fish communities (Zaret and Rand, 1971;Johnson and Johnson, 1982). Studies on the food habits of predacious macroinvertebrate predators are similar in scope and design to the fish studies, ranging from individual species to studies of co-occurring predators in a stream community (Tartar and Krumholz, 1971;Stewart et al, 1973;Winterbourn, 1974;Devonport and Winterbourn, 1976;Hildrew and Townsend, 1976;Seigfried and Knight, 1976;Fuller andStewart, 1977, 1979;Kovalak, 1978;Allan, 1982;Johnson, 1981Johnson, , 1983. These studies provide a wealth of information on what is eaten by different species and often give some information on prey selection or avoidance, usually based on comparisons of diet composition with samples of prey availability.…”
Section: Introductionmentioning
confidence: 99%
“…Coloburiscus, Nesameletus (Ephemeroptera); Stenoperla, Zelandoperla, Zelandobius (Plecoptera); Hydrobiosis, Psilochorema, Pycnocentria, Olinga, Aoteapsyche (Trichoptera); Archichauloides (Megaloptera); Potamopyrgus (Gastropoda) . This similarity arises largely because many New Zealand aquatic insects have broad habitat requirements , show little evidence of food specialisation (Winterbourn 1974(Winterbourn , 1978aCrosby 1975;Devonport & Winterbourn 1976;Davis & Winterbourn 1977;Cowie 1980), and possess flexible, poorly synchronised life histories (Winterbourn 1978b;Cowie 1980;Towns 1981Towns , 1983. In the three streams we studied, virtually all of the above genera were present, and species lists for the streams were remarkably similar.…”
Section: Discussionmentioning
confidence: 99%
“…A shift from daytime to nighttime drifting within a taxon has been reported for B. bicaudatus (this study), P. haterale cited above, DeZeatidium sp. (Ephemeroptera) (Devonport and Winterbourn 1976), Amiocentrus aspilus (Trichoptera) (Anderson 1967), HeZicops yche borealis and some Limnephilidae (Bishop and Hynes 1969).…”
Section: Invertebratesmentioning
confidence: 99%